(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
It is a notable actual peculiarities when a permeable media is totally immersed with a non-wetting liquid. For instance, water is brought into contact. The last option will more often than not precipitously stream into the medium, dislodging the non-wetting liquid. In this paper, we utilize indispensable personalities with intersecting hyper-mathematical series to address the progression of two immiscible fluids in a broke permeable medium. The methodology adopted for the solution is followed by transform of non-linear differential system into an ordinary differential equation. Subsequently obtained equation is convert into diffusion equation by applying similarity variable by standard transformation and further transfer into the confluent hyper geometric equation. The acquired arrangement as far as intersecting hyper mathematical series give an articulation for wetting stage immersion. The outcomes exhibit the straightforward examination to acquire a scientific arrangement of the non direct differential condition of imbibitions peculiarity under extraordinary condition in a broke permeable media wherein the water infiltrating the crease along the broke is sucked into the squares of rock under the activity of hairlike powers and how much water entering the square in the rudimentary volumE